Acoustic signature reveals blue whales tune life‐history transitions to oceanographic conditions. (14th February 2022) - Oestreich, William K.; Abrahms, Briana; McKenna, Megan F.; Goldbogen, Jeremy A.; Crowder, Larry B.; Ryan, John P.
Abstract: Matching the timing of life‐history transitions with ecosystem phenology is critical for the survival of many species, especially those undertaking long‐distance migrations. As a result, whether and how migratory populations adjust timing of life‐history transitions in response to environmental variability are important questions in ecology and conservation. Yet the flexibility and drivers of life‐history transitions remain largely untested for migratory marine populations, which contend with the unique spatiotemporal dynamics and sensory conditions found in marine ecosystems. Here, using an acoustic signature of blue whales' regional population‐level transition from foraging to breeding migration, we document significant interannual flexibility in the timing of this life‐history transition (spanning roughly 4 months) over a continuous 6‐year study period. We further show that variability in the timing of this transition follows the oceanographic phenology of blue whales' foraging habitat, with a later transition from foraging to breeding migration occurring in years with an earlier onset, later peak and greater accumulation of biological productivity. These findings indicate that blue whales delay the transition from foraging to southward migration in years of the highest and most persistent biological productivity, consistent with the hypothesis that this population maximizes energy intake on foraging grounds rather than departing towards breeding grounds as soon as sufficient energy reserves are accumulated. The use of flexible cues (e.g. foraging conditions and long‐distance acoustic signals) in timing a major life‐history transition may be key to the persistence of this endangered population facing the pressures of rapid environmental change. Furthermore, these results extend theoretical understanding of the flexibility and drivers of population‐level migration to a relatively solitary marine migrant. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.